264 Intertrochantic Hip Fracture Fixation at Musgrove Park Hospital. (4th May 2021) - Latif, R; Macdonald, H; Griffith, A; Kelly, A
Abstract: Background: Hip fractures, the commonest fragility fracture in the UK, carry a 6.7% 30-day mortality. NICE-CG124 guide advises extramedullary implants for trochanteric (AO3.1A1/2) and intramedullary nails for subtrochanteric fractures. We carried out a retrospective study on the use of cephalomedullary nails (CMN) at MPH to determine compliance with CG124. Method: National Hip Fracture Database (NHFD) from 2019 was reviewed. Trust records were used for fracture type, surgery, and reasons for deviation from CG124. Results: 201 fractures were identified. NHFD revealed 38 A3 fractures of which 36 underwent CMN, one SHS and one non-operative management. Of 163 A1/A2 fractures, 33 received CMN and 130 CHS. Only 77% of the NHFD data was correct. Further analysis revealed 18 CMNs were used for AO1/2 injuries. All had justifiable reasons for deviation from CG124, although not documented. Conclusions: There is scope to improve accuracy of NHFD data. Deviation from guidelines may be appropriate but reasons must be documented and, when appropriate, discussed with patient. Similar nationwide inaccuracy can have significant implications for research based upon NHFD data. To prevent input of incorrect data, our recommendations include: Consultant to confirm AO grade during trauma meetings Reason CMN used for AO1/2 fractures to be documented Monthly local NHFD data audit